The Effect Of Students' Learning Motivation And Learning Interest On The Outcomes Of Social Sciences Learning Of Grade VII Students - Oktaviana Dasalak; Benjamin Albert Simamora; Eduward Situmorang (CV Putra Publisher, 2026)
The problem in this study is the low learning outcomes of students in social studies, which is suspected to be influenced by a lack of learning motivation and low interest in learning. This study aims to determine the influence of learning motivation and interest on social studies learning outcomes of grade VII students at the UPTD of SMP Negeri 1 Pematangsiantar. This research is quantitative and uses descriptive methods. The study population was all students in grades VII/1-VII/10, totaling 320 students. Sampling was conducted using proportional random sampling, resulting in a sample size of 80 students. Data were collected through a questionnaire for the variables of learning motivation and learning interest, as well as daily test scores for social studies as learning outcomes. Data analysis techniques used included simple linear regression, multiple linear regression, t-test, F-test, and coefficient of determination. The analysis requirements were tested for normality using chi-square, based on the calculation of both variables' normal distribution. The analysis results showed a positive and significant effect of learning motivation on student learning outcomes, with a calculated t-value of X1 of 2.008 with a significance value (α) of 0.048, meeting the significance requirement of <0.05. Therefore, the calculated t-value (2.008) is greater than the t-table (1.668), and a significance value (α) of 0.048 <0.05. Furthermore, there is a positive and significant effect of learning interest on student learning outcomes, with a calculated t-value of X2 of 2.011 with a significance value (α) of 0.048, meeting the significance requirement of 0.05. Thus, the calculated t-value (2.011) is greater than the calculated t-value (1.668), and the significance value (α) is 0.048, <0.05. The F-test results indicate that both variables simultaneously have a significant effect on student learning outcomes, amounting to 15.851 with a significance level (α) of 0.000. The F-table value is 3.114. Therefore, the calculated F-value (15.851) is greater than the F-table (3.095), and the significance level (α) is 0.000 <0.05. The coefficient of determination (R²) of 0.272 indicates that 27.2% of the variation in student learning outcomes is influenced by learning motivation and learning interest, while the remaining 72.8% is influenced by other factors not examined in this study